Body mass index trajectories from 2 to 18 years – exploring differences between European cohorts. Issue 2 (26th February 2016) - Graversen, L.; Howe, L. D.; Sørensen, T. I. A.; Sovio, U.; Hohwü, L.; Tilling, K.; Laitinen, J.; Taanila, A.; Pouta, A.; Järvelin, M‐R.; Obel, C.
Summary: Background: In recent decades, there has been an increase in the prevalence of childhood overweight in most high‐income countries. Within northern Europe, prevalence tends to be higher in the UK compared with the Scandinavian countries. We aimed to study differences in body mass index (BMI) trajectories between large cohorts of children from UK and Scandinavian populations. Methods: We compared BMI trajectories in participants from the English Avon Longitudinal Study of Parents and Children born in 1991–1993 (ALSPAC) (N = 6517), the Northern Finland Birth Cohorts born in 1966 (NFBC1966) (N = 3321) and 1986 (NFBC1986) (N = 4764), and the Danish Aarhus Birth Cohort born in 1990–1992 (ABC) (N = 1920). We used multilevel models to estimate BMI trajectories from 2 to 18 years. We explored whether cohort differences were explained by maternal BMI, height, education or smoking during pregnancy and whether differences were attributable to changes in the degree of skew in the BMI distribution. Results: Differences in mean BMI between the cohorts were small but emerged early and persisted in most cases across childhood. Girls in ALSPAC had a higher BMI than all other cohorts throughout childhood, e.g. compared with the NFBC1986 BMI was 2.2–3.5% higher. For boys, the difference emerging over time (comparing the two NFBC's) exceeded the differences across populations (comparing NFBC1986, ABC and ALSPAC). BMI distribution demonstrated increasing right skew with age. Conclusion: Population‐level differences between cohorts were small, tended to emerge very early, persisted across childhood, and demonstrated an increase in the right‐hand tail of the BMI distribution.